Efficiency conversion of jatropha oil into high-quality biofuel over the innovative Ni-Mo2N based catalyst. (15th September 2022) - Lei, Xiaomei; Xin, Hui; Du, Xiangze; Yang, Huiru; Zeng, Yan; Zhou, Linyuan; Juan, Chao; Zhang, Hualong; Li, Dan; Hu, Changwei
Graphical abstract: Highlights: Ni-Mo2 N catalyst can be effectively convert jatropha oil into high-quality biofuel. The HDO performance of Ni-Mo2 N is significantly improved than that of Mo2 N. The synergy of Ni and Mo2 N assists in high biofuel yield and deoxygenation ability. The interaction between metal and support would affect the deoxygenation pathway. Abstract: Mo2 N catalyst can effectively remove oxygen from biomass oil under harsh reaction conditions. Herein, the innovative Ni-Mo2 N/γ-Al2 O3 catalyst was synthesized through conventional impregnation method and NH3 or N2 /H2 pretreatment. The hydrodeoxygenation performance of Ni-Mo2 N/γ-Al2 O3 catalyst is significantly improved in comparison with Mo2 N. At 320 °C and 3 MPa, the oxygen of jatropha oil is completely removed and high-quality biofuel with high selectivity of C15 -C18 hydrocarbons are obtained over the Ni-Mo2 N/γ-Al2 O3 catalyst. This good reactivity for Ni-Mo2 N/γ-Al2 O3 catalyst are ascribed to the synergistic effect of Ni and Mo2 N, the most uniform Ni dispersion and the excellent coke resistance ability. Ni, as an auxiliary, is conductive to the cleavage of H–H bonds, while Mo2 N are beneficial to the cleavage of C–O bonds. In addition, the metal-support interaction would affect the deoxygenation pathway of jatropha oil. This research proposes an efficient strategy for enhancing the hydrodeoxygenation performance of Mo2 N catalysts for the jatropha oil conversion.